Menumbuhkan Minat Menabung Mahasiswa: Pengaruh Literasi Keuangan Islam, Motivasi, Digitalisasi, dan Kepercayaan - Hasibuan, Siti Halimah; Nasution, Anriza Witi; Zulhendry, Zulhendry; Zuardi, Muhammad; Nuraini, Nuraini (Jurnal EMT KITA, 2026)
This study aims to examine the influence of Islamic financial literacy, saving motivation, service digitalization, and trust on students’ interest in saving at Bank Syariah Indonesia. Primary data were collected through questionnaires distributed to 60 students of the Islamic Finance and Banking Study Program at Medan State Polytechnic. The study employed a quantitative approach using a Likert-scale instrument. The collected data were analyzed using multiple linear regression with SPSS version 26. The findings indicate that Islamic financial literacy (t hitung = 2,842; Sig. = 0,006) and trust (t hitung = 5,001; Sig. = 0,000) have a positive and significant effect on students’ interest in saving, while saving motivation (t hitung = 0,373; Sig. = 0,711) has no significant effect. Conversely, service digitalization (t hitung = -2,166; Sig. = 0,035) shows a negative and significant effect on saving interest. Simultaneously, the four independent variables jointly have a positive and significant influence on saving interest at Bank Syariah Indonesia. The coefficient of determination (R²) of 0.633 suggests that 63.3% of the variation in saving interest can be explained by the four independent variables, while the remaining 36.7% is attributed to other factors not examined in this study.